THE IMPORTANCE OF DEANTOLOGY IN THE PRAKTICE OF THERAPEUTIC DENTISTRY - Abdukholikov Samandar Khamidulloyevich; Sanakulov Olmosjon Nizomjon o’g’li; Zoyirov Tolkin Elnazarovich (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
This article is devoted to deontological aspects in dentistry. The science of dentistry teaches the doctor to treat the patient not as an object of his observations and therapeutic actions, but as an individual with his own spiritual world, his desires, hopes, concerns, and fears. Each person is an individual.